The decarbonization potential of dryland silvopastoral systems - Philp, Joshua; Vinceti, Barbara; Herrera, Pedro (2024)
Silvopastoral systems (SPS), which integrate trees and grazing, have proven effective for sustainable land management. Globally, SPS can store 68 to 204 Mg of CO₂ per hectare, though this capacity varies based on ecological conditions, management practices, and site history. Enhancing carbon sequestration potential requires improvements in SPS design and maintenance, focusing on tree and shrub management, grass and forage care, livestock grazing practices, soil health, and economic strategies. Despite their potential, knowledge gaps hinder investment in SPS to contribute to climate change adaptation and mitigation. To address these gaps, a systematic literature review was initiated to quantify carbon sequestration rates in dryland SPS. Next steps include completing the review, engaging research partners with FAO, mobilizing resources for a global project, and generating recommendations for best SPS management practices tailored to diverse contexts to maximize carbon sequestration.